2011
DOI: 10.1016/j.pscychresns.2010.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Atypical modulation of medial prefrontal cortex to self-referential comments in generalized social phobia

Abstract: Generalized social phobia (GSP) involves the fear of being negatively evaluated. Previous work suggests that self-referentiality, mediated by medial prefrontal cortex (MFPC), plays an important role in the disorder. However, it is not clear whether this anomalous MPFC response to selfrelated information in patients with GSP concerns an increased representation of their own or others' opinions. In this paper we examined whether GSP is associated with increased response to own (1 st person) or other individuals'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 55 publications
7
73
0
Order By: Relevance
“…The self-referential network has been associated with the inhibition or extinction of excessive corticolimbic activity (LeDoux, 1998) and altered self-reference in SAD (Blair et al, 2011;Liao et al, 2010). As there is a prominent cognitive behavioral model of SAD, which hypothesizes a tendency toward increased self-awareness and monitoring as a response to fear of being observed and evaluated by others (Liao et al, 2010;Rapee and Heimberg, 1997), our results indicated alteration of self-referential processing, even in nonclinical populations.…”
Section: Discussionmentioning
confidence: 52%
“…The self-referential network has been associated with the inhibition or extinction of excessive corticolimbic activity (LeDoux, 1998) and altered self-reference in SAD (Blair et al, 2011;Liao et al, 2010). As there is a prominent cognitive behavioral model of SAD, which hypothesizes a tendency toward increased self-awareness and monitoring as a response to fear of being observed and evaluated by others (Liao et al, 2010;Rapee and Heimberg, 1997), our results indicated alteration of self-referential processing, even in nonclinical populations.…”
Section: Discussionmentioning
confidence: 52%
“…Previous work has shown that this population shows heightened medial frontal cortical responses to self-relevant material (Blair et al . 2008 a , 2010, 2011 b ; Goldin & Gross, 2010). Moreover, self-referential processing has been shown to recruit the cortical midline structure from ventromedial and rostral regions to the posterior cingulate cortex (Amodio & Frith, 2006; Northoff et al .…”
Section: Discussionmentioning
confidence: 99%
“…In another dissociation, healthy controls and individuals with social phobia (who fear being negatively evaluated by others) were exposed to evaluative phrases that were presented either in the first person (e.g., “I’m ugly”) or in the second person (e.g., “You’re ugly”). Healthy controls had higher vmPFC activity during first- versus second-person phrases, whereas individuals with social phobia had higher vmPFC activity during the reverse contrast (23) – presumably of high personal relevance to this psychopathology.…”
Section: The Racc/vmpfc: Emotionally Tagging Stimuli For Personal Relmentioning
confidence: 98%